A Study to Evaluate the Effectiveness of Structured Teaching Module on Prevention of Anemia among Adolescent Girl at Selected School in Kotdwar - Kaparwan, Mamta (Indian Journal of Nursing Sciences, 2024)
Aim: The aim of this study was to assess the prevalence of anemia and associated factors among school adolescent girls at selected school in Kotdwar. Objectives: The objectives of this study were as follows: (1) To evaluate the effectiveness of planned teaching program on iron deficiency anemia and its management. (2) To find out the association between pre-test level of adolescence girl with their demographic variables. Materials and Methods: Pre-experimental research design was adopted and non-probability convenient sampling technique was used to select the sample. The study was conducted in rural school of Kotdwar, where 300 samples who satisfied the inclusion criteria and gave voluntary consent for the study were selected. STP for assessing the “knowledge of adolescent girls regarding iron folic acid deficiency anemia” was used to collect data from the samples. Results: The finding of the study shows (61.3%) adolescent girls that had inadequate knowledge, 33.63% had moderate knowledge, and only 5% had adequate knowledge, during the pre-test. After giving structured teaching program (post-test), 90.63% adolescent girls scored adequate knowledge that only 9.3% come under moderate knowledge and 0.3% comes under inadequate knowledge. Association of demographic variables with the pre-test level of knowledge was done using Chi-square test. There was a statistical significant association found between level of knowledge and demographic variable such as age, education, and previous exposure at P = 0.05 levels. Hence, the research hypothesis “there will be an association between pre-test knowledge scores of care givers with their selected demographic variables” is accepted. Conclusion: The overall prevalence of anemia among adolescent females was found to be 90%. There is significant association of anemia with socioeconomic status and parents’ educational status. There is need to increase awareness of anemia in adolescent girls and parents.